Modification of Grocott's staining procedure with heat treatment and oxidation by periodic acid for mucormycosis in tissue: a method to detect Mucor spp. - Yayoi Kawabata Kamo; Hisaki Igarashi; Haruhiko Sugimura (BioTechniques, 2023)
The sensitivity of the Grocott-modified Gomori's methenamine-silver nitrate technique for the detection of fungi is sometimes low, especially for Mucor spp. We modified the Grocott technique by replacing chromic acid with periodic acid in the oxidation step. The use of periodic acid instead of chromic acid enhanced the detectability of Mucor spp. in histopathological sections. Other parameters should be assessed with a high number of cases under different conditions. We propose our protocol as one of the options in practice, especially in cases suspected of Mucor spp. infection.